2021
DOI: 10.1016/j.jacc.2021.07.055
|View full text |Cite
|
Sign up to set email alerts
|

Troponin-Guided Coronary Computed Tomographic Angiography After Exclusion of Myocardial Infarction

Abstract: Background Patients with suspected acute coronary syndrome in whom myocardial infarction has been excluded are at risk of future adverse cardiac events. Objectives This study evaluated the usefulness of high-sensitivity cardiac troponin I (hs-cTnI) to select patients for further investigation after myocardial infarction has been excluded. Methods This is a prospective cohort study of patients presenting to the emergency department with suspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 51 publications
1
18
0
1
Order By: Relevance
“…The PRECISE-CTCA study was a single-centre prospective cohort study enrolling 250 patients with suspected acute coronary syndrome presenting to the Royal Infirmary of Edinburgh, Edinburgh, Scotland 9. Smoking history was categorised into any history of smoking versus never smoked.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PRECISE-CTCA study was a single-centre prospective cohort study enrolling 250 patients with suspected acute coronary syndrome presenting to the Royal Infirmary of Edinburgh, Edinburgh, Scotland 9. Smoking history was categorised into any history of smoking versus never smoked.…”
Section: Methodsmentioning
confidence: 99%
“…The PRECISE-CTCA study (Troponin Within the Normal Reference Range to Risk Stratify Patients With Acute Chest Pain for Computed Tomography Coronary Angiography; ClinicalTrials.gov number NCT04549805) demonstrated that coronary artery disease was three times more likely in patients without myocardial infarction who had intermediate cardiac troponin compared with those with low concentrations 9. However, newer diagnostic approaches can go beyond the assessment of coronary stenosis to define plaque characteristics and identify high-risk atherosclerosis associated with acute coronary syndromes 10.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy is in agreement with findings from the large PROMISE trial, where cTn was not only associated with higher coronary artery calcium score in a population with suspected coronary artery disease [13], but patients in the lowest cTn-quartile had significantly lower 1-year risk of MI, UAP or death (0.8%) compared to the higher quartiles (1.5%, 2.4% and 3.2%, respectively) [14]. In patients presenting to the emergency department with suspected ACS, but who had MI excluded, CAD was 3-fold more prevalent in those with moderately elevated cTnI, compared to those with low concentrations (<5 ng/L) [15]. Thus, measurements of cardiac biomarkers integrated with thorough clinical assessment may be a readily available, low-cost strategy in managing patients with suspected coronary syndromes.…”
Section: Discussionmentioning
confidence: 84%
“…The authors demonstrated that CAD was 3 times more likely in patients who had slightly elevated levels of hs-cTnI compared to those with low values of serum hs-cTnI, indicating that CCTA added to routine hs-TnI determination could improve the diagnosis of chronic coronary syndromes in patients presenting to the ED for chest pain. 23 However, in another study published recently, Wang et al demonstrated that the cardiac troponin at presentation had no significant effect on the clinical impact of early CCTA in intermediate-risk patients presenting to the ED for chest pain. The rate of noninvasive and invasive testing, coronary revascularization, and the primary outcomes were not significantly influenced by the values of cardiac troponin (p for interaction 0.33 for noninvasive test, 0.33 for invasive tests, and 0.57 for PCI).…”
Section: Ccta and Cardiac Biomarkers In The Edmentioning
confidence: 98%